When the political becomes (painfully) personal: Org-studying the consequences of Brexit. (May 2020) - Kerr, Ron; Śliwa, Martyna
This 'Speaking Out' essay contributes to debates over Brexit and populism by suggesting how we, as management and organisation studies scholars, might approach 'org-studying' Brexit. First, as UK-based European Union citizens working in UK business schools, we clarify our own position(s) in relation to Brexit. Second, we position ourselves more specifically as management and organisation studies academics by considering how we might begin to analyse the organisational consequences of Brexit through seeing it as part of a continuing global crisis – or series of crises – including and going beyond those affecting American and European societies and economies, as well as their political and other social fields and organisations. We highlight the salience of emotions with regard to Brexit, and in particular ressentiment in relation to populism as a political methodology. We also note the importance of identity and how political and personal identities are being reconstituted in the United Kingdom in light of the Brexit vote. We put forward suggestions for how management and organisation studies scholars might integrate these insights into an overarching approach to researching the organisational consequences of Brexit based on the works of Pierre Bourdieu and Gisèle Sapiro on the transposition of crisis. Our final remarks address the way that Brexit crisis continues to challenge our own established identities.